Energy-linked Efficiency in Mediterranean Container Ports under Decarbonization Pressures - Mchirgui, Dirin; Sellami, Sameh Zouari (Journal of Posthumanism, 2025)
This study reconsiders port efficiency by treating energy consumption as a productive input that can expand throughput, rather than a mere cost. We develop a stochastic frontier analysis (SFA) framework in which output is throughput (e.g., TEU) and inputs include land, labor, and energy, allowing energy to constrain or amplify productive capacity. Leveraging a panel of 40 Mediterranean container ports over 2022–2024, we decompose technical inefficiency (TE) into input-specific components and quantify the contributions of labor and energy to underperformance. The analysis builds canonical SFA formulations (Aigner, Lovell, & Schmidt, 1977; Farrell, 1957) with panel extensions (Battese & Coelli, 1995), introducing energy as a central input linked to both throughput and emissions outcomes. Results reveal a stratified regional landscape: mega-hubs such as Tanger Med, Valencia, and Piraeus operate near the technical frontier, while many gateway and regional ports, particularly in North Africa and the Eastern Mediterranean, exhibit notable inefficiency. Crucially, input-specific decompositions show labor and energy jointly accounting for over half of total inefficiency in mid- and low-tier ports, signaling that suboptimal resource management not infrastructure alone drives performance gaps. The study contributes to decarbonization discourse by framing energy efficiency as a driver of throughput, with implications for policy and investment in energy management and green port technologies.